Severity of Depression Predicts Remission Rates Using Transcranial Magnetic Stimulation - Grammer, Geoffrey G.; Kuhle, Andrew R.; Clark, Caroline C.; Dretsch, Michael N.; Williams, Kathy A.; Cole, Jeffrey T. (Frontiers in Psychiatry, 2015)
Background: Multiple factors likely impact response and remission rates in the treatment of depression with repetitive transcranial magnetic stimulation (rTMS). Notably the role of symptom severity in outcomes with rTMS is poorly understood. Objective/Hypothesis: This study investigated the predictors of achieving remission in patients suffering from depression who receive ≥3 rTMS treatments per week. Methods: Available data on 41 patients treated at Walter Reed National Military Medical Center from 2009 to 2014 were included for analysis. Patients received a range of pulse sequences from 3,000 to 5,000 with left sided or bilateral coil placement. Primary outcome measures were total score on the Patient Health Questionnaire (PHQ-9) or the Quick Inventory of Depressive Symptomatology—Self Rated (QIDS-SR). Remission was defined as a total score less than five, and response was defined as a 50% decrease in the total score on both outcome metrics. Outcomes in patients diagnosed as suffering from mild or moderate depression were compared to those suffering from severe depression. Results: Of the 41 patients receiving treatment, 16 reached remission by the end of treatment. Remission rate was associated with the initial severity of depression, with patients with mild or moderate depression reaching remission at a significantly higher rate than those with severe depression. Total number of rTMS sessions or length of treatment were not predictors of remission. Conclusion: Patients with a baseline level of depression characterized as mild or moderate had significantly better outcomes following rTMS compared to patients with severe depression.